2005
DOI: 10.1016/j.femsle.2005.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A rapid screening test to distinguish betweenCandida albicansandCandida dubliniensisusing NMR spectroscopy

Abstract: Nuclear magnetic resonance (NMR) spectroscopy combined with a statistical classification strategy (SCS) successfully distinguished between Candida albicans and Candida dubliniensis. 96% of the isolates from an independent test set were identified correctly. This proves that this rapid approach is a valuable method for the identification and chemotaxonomic characterisation of closely related taxa. Most discriminatory regions were correlated with metabolite profiles, indicating biochemical differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Analysis of the endometabolomes of different strains of Escherichia coli by two‐dimensional high‐performance thin‐layer chromatography showed a wide range of biodiversity that correlated well with the genetic relationships among strains (Maharjan and Ferenci, 2005). Similary, metabolomic analysis of whole cells from different Candida species by nuclear magnetic resonance spectroscopy provided a rapid method for identification and intra‐specific strain discrimination (Himmelreich et al , 2003, 2005). The results presented here show that the exometabolome may be used to discriminate and classify industrial yeast strains and provide a new approach for chemotaxonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the endometabolomes of different strains of Escherichia coli by two‐dimensional high‐performance thin‐layer chromatography showed a wide range of biodiversity that correlated well with the genetic relationships among strains (Maharjan and Ferenci, 2005). Similary, metabolomic analysis of whole cells from different Candida species by nuclear magnetic resonance spectroscopy provided a rapid method for identification and intra‐specific strain discrimination (Himmelreich et al , 2003, 2005). The results presented here show that the exometabolome may be used to discriminate and classify industrial yeast strains and provide a new approach for chemotaxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the genetic complexity inherent in the brewing yeast species can result in misclassification and genetic methods do not always allow reliable separation of closely related strains. The metabolome (collection of low molecular weight organic and inorganic chemical species present in a cell or biological system) can detect genotypic and phenotypic differences in yeast (Oliver, 1998; Raamsdonk et al , 2001; Himmelreich et al , 2003, 2005) and is expected theoretically, and has been shown experimentally, to have a greater discriminatory power than transcriptomics and proteomics (Kell and Westerhoff, 1986; Urbanczyk‐Wochniak et al , 2003). The aim of the present work was thus to use a metabolomics approach for the chemotaxonomy of brewing yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the presence and the quantity of small molecule metabolites simultaneously, this tool can be used for researchers to determine the effects caused by perturbations on the host's metabolic profiles. Nevertheless, the use of standardized conditions, growth media and pure cultures of isolates are required to ensure reproducible and accurate identification (Himmelreich et al, 2003(Himmelreich et al, , 2005(Himmelreich et al, , 2017Sandrin et al, 2013;Vitali et al, 2015;Foschi et al, 2017;Oliver et al, 2020). Metabolomic profiles of vaginal secretions can also be determined by gas (GC-MS) and liquid chromatography and mass spectrometry (LC-MS).…”
Section: Analysis Of Vaginal Microbiome and Metabolomementioning
confidence: 99%
“…dubliniensis . Accuracy of identifi cation was 96%, compared with 90% for the commercial biochemical identifi cation methods, VITEK YBC or API ID32 (both from bioMérieux, Inc., Marcy l'Etoile, France), when performed on germ tube positive Candida spp [ 9 ].…”
Section: Identifi Cation Of Fungi Cultured In Vitromentioning
confidence: 99%